Analysis of Utilization of Hospital Management Information System (SIMRS) In Ibnu Sina Hospital YW-UMI Makassar - Muhammad Ridwan Rumasukun; Mohammad Aldrin Akbar; Rismawati Rismawati; Sabri Hasan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The development of technological advances today is growing very rapidly. Currently, in various fields, an application system is needed which makes it a must for every agency, both government and private, in data management that utilizes information as the basis for technology-based administration. The most important role in providing clinical services administratively with the use of information systems must be owned by the hospital. At this time the management of information in hospitals has been implemented with the use of an electronic-based information system (SIMRS), every hospital requires a management information system (SIM) in improving the quality of medical services carried out. In an integrated hospital environment information system (SIMRS) whose design can be used for all hospital activities into one integrated system so that it can be stored in a central database. The application of the use of applications that are stored in an existing case, data, and problems so that they can be turned into something new without losing the basic values of the data, problems, and work itself.